Public Attitudes Toward Priority Setting Principles in Health Care During COVID-19 - Tinghög, Gustav; Strand, Liam (Frontiers in Health Services, 2022)
What role should cost-effectiveness play in health care priority setting? We assess the level of acceptance toward different priority setting principles in health care during COVID-19 and in general, thereby exploring public support for principles presented at different levels of abstraction. An online survey was distributed to a diverse sample of the Swedish population (n = 1 553). The results show that respondents were generally more supportive of priority setting principles when expressed in general abstract terms than when expressed in more case specific concrete terms. However, prioritization based on cost-effectiveness was deemed as more acceptable when expressed in concrete terms related to health maximization rather than as an abstract principle. Respondents had a general inclination in support of physicians and other health care professionals the primary responsibility for the allocation of scarce resources in the healthcare during COVID-19, while being less supportive of health economists and politicians being involved in these decisions.